Tunable Fabrication of CuO Nanoplates on ZnO Nanorods: Heterostructure Formation by Photodeposition for Enhanced Photocatalytic Activity. Issue 21 (21st May 2019) - Zhang, Jiejing; Gao, Shiyong; Wang, Guangning; Ma, Xinzhi; Jiao, Shujie; Sang, Dandan; Liu, Shuo; Mao, Mouwen; Fang, Haitao; Wang, Jinzhong
Abstract : CuO nanoplates (NPs) have been prepared on ZnO nanorods (NRs) to form heterostructure by a simple photodeposition method at room temperature. The morphology, composition, and structure of the as‐prepared CuO NPs/ZnO NRs heterostructure were analyzed by SEM, TEM, XPS, and XRD. UV/Vis absorption spectrum indicates that the CuO NPs/ZnO NRs heterostructure exhibits a strong absorption in both the UV and visible light region. Photocurrent response results and the photoluminescence spectrum confirm that the CuO NPs/ZnO NRs heterostructure could promote the separation of photogenerated carriers. The photocatalytic ability of the as‐prepared samples was evaluated by degrading methyl orange. Moreover, the possible growth and photocatalytic mechanisms of the CuO NPs/ZnO NRs heterostructure were discussed. Abstract : CuO nanoplates have been prepared on ZnO nanorods by a facile photodeposition method at room temperature. The as‐prepared CuO nanoplates/ZnO nanorods heterostructure exhibited high photocatalytic performance and good recyclability. In addition, the amount of CuO nanoplates has an effect on the photocatalytic activity.